2021
DOI: 10.1111/ans.17378
|View full text |Cite
|
Sign up to set email alerts
|

Receiver operating characteristic curve analysis of arteriovenous dialysis access flow using ultrasound

Abstract: Backgrounds: Despite numerous studies investigating the use of ultrasound (US) in assessing arteriovenous fistulas (AVF), there are no universally agreed threshold flow velocities in diagnosing significantly abnormal flow that are useful in predicting thrombotic flowrelated dysfunction. This study evaluates a predictive model using receiver operating characteristic curve (ROC) analyses to establish threshold velocities. Methods: Five hundred and eleven US scans were analysed. ROC curves were used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…shown that the chief determinant of Qa is the TAMV and the other less predictive parameters are EDV and PSV. 21 The mean BD of the forearm and arm AVF at 5.5 and 5.6 mm are not significantly different and again confirms that differing haemodynamics account for different Qa between the two AVF configurations.…”
Section: Test Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…shown that the chief determinant of Qa is the TAMV and the other less predictive parameters are EDV and PSV. 21 The mean BD of the forearm and arm AVF at 5.5 and 5.6 mm are not significantly different and again confirms that differing haemodynamics account for different Qa between the two AVF configurations.…”
Section: Test Resultsmentioning
confidence: 52%
“…Even so, these levels do not differentiate between the configuration of the AVF, that is, forearm or arm AVF even though the differing haemodynamics and complications between the two configurations have been well established 6,7,20 . We have also previously shown that the chief determinant of Qa is the TAMV and the other less predictive parameters are EDV and PSV 21 . The mean BD of the forearm and arm AVF at 5.5 and 5.6 mm are not significantly different and again confirms that differing haemodynamics account for different Qa between the two AVF configurations.…”
Section: Discussionmentioning
confidence: 93%
“…A study by Yii et al [18] assessed 511 AVFs and analyzed the ROC curves for TA mean, PSV, and EDV as predictive for thrombotic flow-related AVF dysfunction. They concluded that TA mean cutoffs of 45 cm/s for forearm AVFs and 49 cm/s for arm AVFs yielded the best AUC values (0.95).…”
Section: Thrombosismentioning
confidence: 99%